Effectiveness of the proposed training formative assessment programme and its ımpact on teaching style ımprovements of saudi science teachers in saudi arabia - Alanazı, Fayadh Hamed (Journal of Turkish Science Education, 2017)
This work investigates the effects associated with training initiatives consistent with formative assessment to enhance teaching among science teachers in Saudi primary schools. The programme comprised training sessions that were ongoing for a period of two months, which emphasised the strategic skills of adopting the formative assessment. The researcher adopted an experimental approach centred on the design of the control and experimental groups to establish the overall efficiency of the suggested training programme in the development of knowledge among teachers in the field of formative assessment strategy skills. The sample comprised 33 primary school science teachers who were based in Sakaka in the Al-Jouf region; the sample was randomly divided into an experimental group (16 teachers) and a control group (17 teachers). The findings indicate the success of the proposed program, in which the experimental group was more a function of the control group in the telemetric measurement. Moreover, classroom observations were applied by the researcher, in which the science teachers were assessed with the aim to determine whether a form of formative assessment was used following the completion of the programme. The findings suggest that the science teachers adopted various strategies of formative assessment, including sharing learning goals, open questions, assessment-based evidence, and teacher– child classroom dialogue.
Keywords: Science teachers; summative assessment; formative assessment; training program; teaching